The genetic and environmental relationship between Cloninger’s dimensions of temperament and character - Gillespie, Nathan A. (Pers Individ Dif, 2003)
The purpose of this study was to determine whether Cloninger’s revised 7-factor model of personality showed incremental validity over his four dimensions of temperament. A sample of 2517 Australian twins aged over 50 between 1993 and 1995 returned completed self-reported measures of Self-directedness, Cooperativeness, and Self-transcendence from Cloninger’s Temperament and Character Inventory. Many of these twins had participated in a 1988 study containing Cloninger’s temperament measures of Harm Avoidance, Novelty Seeking, Reward Dependence and Persistence. Contrary to theoretical expectations, univariate analyses revealed that familial aggregation for the character dimensions could be entirely explained by additive gene action alone. Although temperament explained 26, 37 and 10% of additive genetic variance in Self-directedness, Cooperativeness and Self-transcendence, respectively, seven genetic factors were required to explain the genetic variance among the TPQ dimensions, and almost all of the non-shared environmental variance was unique to each dimension of character. Our results indicate that the inclusion of all seven dimensions in a taxonomy of personality is warranted.